REABILITAÇÃO FISIOTERAPÊUTICA EM UM PACIENTE COM TENDINOSE BICIPITAL NA ATENÇÃO PRIMÁRIA: RELATO DE CASO - GOMES DE FREITAS, PEDRO AUGUSTO; OLIVEIRA VIANA, SABRINA; COLAMARCO FERREIRA RESENDE, MÁRCIA (Sinapse Múltipla, 2019)